EVALUATING THE EFFECTS OF THE COUNTERINSURGENCY ON BOKO HARAM IN NIGERIA - Sadjere, Godwin Ejuvwedia; Onyiriuka, Ekene Jude; Mbam, Justice Chinedu; Ikponmwonba, Eloghosa Anderson; Onyiriuka, Ngozi Palmer; Afolabi, Samuel Adedeji (Journal of Terrorism Studies, 2025)
Boko Haram insurgency debuted in Nigeria in 2009 and has been on for more than eleven years and has become intractable even after the government instituted a counterinsurgency in 2013. This paper analysed the effect of the counterinsurgency on Boko Haram and the insurgency in Nigeria in general based on attacks by the insurgents. Historical data on attacks by Boko Haram and other criminal groups were collected using web scraping by Python and subjected to statistical analysis to build a relationship between the insurgency and the counterinsurgency. Eleven years data from 2012 were collected but six years data from 2017 to 2021 after the institution of the counterinsurgency were subjected to Regression analysis to establish a trend between the data; and Chi-square distribution test was used to determine the effect(s) of the six years of counterinsurgency. The Regression analysis showed that the counterinsurgency decreased the incidence of attacks by Boko Haram but did not reduce the insurgency due to the entrant of other players. The Chi-Square analysis inferred that the insurgency is affected by the years of the counterinsurgency, so they cannot be taken as independent events. However, the analysis did not establish the effects of one on the other.